Changes in risk factors for preterm birth in Western Australia 1984–2006. Issue 9 (2nd May 2013) - Hammond, G; Langridge, A; Leonard, H; Hagan, R; Jacoby, P; DeKlerk, N; Pennell, C; Stanley, F
<x xml:space="preserve">Abstract</x> Objective To characterise changing risk factors of preterm birth in Western Australia between 1984 and 2006. Design Population‐based study. Setting Western Australia. Population All non‐Aboriginal women giving birth to live singleton infants between 1984 and 2006. Methods Multinomial, multivariable regression models were used to assess antecedent profiles by preterm status and labour onset types (spontaneous, medically indicated, prelabour rupture of membranes [PROM]). Population attributable fraction (PAF) estimates characterized the contribution of individual antecedents as well as the overall contribution of two antecedent groups: pre‐existing medical conditions (including previous obstetric history) and pregnancy complications. Main outcome measure Antecedent relationships with preterm birth, stratified by labour onset type. Results Marked increases in maternal age and primiparous births were observed. A four‐fold increase in the rates of pre‐existing medical complications over time was observed. Rates of pregnancy complications remained stable. Multinomial regression showed differences in antecedent profiles across labour onset types. PAF estimates indicated that 50% of medically indicated preterm deliveries could be eliminated after removing six antecedents from the population; estimates for PROM and spontaneous preterm reduction were between 10 and 20%. Variables pertaining to previous and current obstetric complications (previous preterm birth, previous caesarean section, pre‐eclampsia and antepartum haemorrhage) were the most influential predictors of preterm birth and adverse labour onset (PROM and medically indicated). Conclusions Preterm antecedent profiles have changed markedly over the 23 years studied. Some changes may be attributable to true change, others to advances in surveillance and detection. Still others may signify change in clinical practice.